KOMUNIKASI ISLAMI DALAM PENDIDIKAN DAN PELATIHAN MODERASI BERAGAMA SEBAGAI MITIGASI KONFLIK SOSIAL KEAGAMAAN: The Role of BDK in Accommodating the Interests of Religious People - Wira, Suhesti Wira Dharma; Syukur Kholil; Rubino (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
The diversity of North Sumatran society makes it vulnerable to socio-religious conflict. The government has made numerous efforts to mitigate these conflicts, one of which is through early detection policies of religious social conflicts based on religious moderation and the development of communication patterns taught in education and training by the Medan Religious Training Center. It is thought necessary to study and analyze communication patterns for conflict resolution in depth so that they can be employed in line with the community's conditions and characteristics. This study took a descriptive qualitative method, with data collected through interviews, participant observation, and document analysis using data triangulation techniques. The findings revealed that, first, efforts to address religious social conflicts must be carried out through religious education and training (improving the quality of human resources), digital transformation of early warning systems (applications Early Warning System), and measurement of the index of religious behavior (Religiosity Index). Second, mechanisms for dealing with religious social conflicts in the society must be established, particularly in terms of more effective communication patterns and transparent transmission of the concept of religious moderation.